Produção e aplicação de enzimas na redução de biofilme de Candida albicans - Queiroz, Geisiany Maria de [UNESP] (2014)
The emergence of Candida albicans biofilms as a form of microbial resistance on solid surfaces is a increasing public health problem, since the effective therapeutic options for the few reduction and elimination, mainly due to its high resistance to antifungals. The enzymes produced by microorganisms attract great interest because they represent an option to biotechnology and antifungal mouthwashes available in the market. The aim of this study was to produce, determine the activity, fractionate three different microbial enzymes (protease, amylase and lipase), and to evaluate the effectiveness in reducing biofilm of C. albicans besides the possible mechanisms of action of these enzymes on the biofilm. For enzyme production were used fungal strains submitted the liquid fermentation in bioreactor, accompanied by study of biochemical parameters of each enzyme. The assessment of effectiveness against biofilms of C. albicans was performed by different methods: Evaluation of the ability to reduce biofilm of C. albicans in microplate 96 wells by XTT; Evaluation of the reduction in the number of colony forming units of biofilm by counting in Sabouraud dextrose agar with chloramphenicol; Evaluation of biofilm reduction capacity of C. albicans in specimens of acrylic resin by XTT and reduction capacity of the number of colony forming units per count Sabouraud dextrose agar with chloramphenicol. In addition, it is also analyzed the influence of these enzymes on virulence factors and the development of biofilm architecture and by analysis in scanning electron microscopy. The three enzymes were effective in reducing assays well microplate as specimens, especially against mature biofilms, 48 hours. The assays in microplates, amylase was the most active enzyme of the three, in contact of 30 minutes, while the protease was more effective in contact of 60 minutes and the lipase was less active in both periods analyzed. However, in specimens, the enzymes ...